Conventional cardiovascular risk factors associated with Takotsubo cardiomyopathy: A comprehensive review. Issue 8 (3rd June 2021) - Liang, Jing; Zhang, Jingyi; Xu, Yidan; Teng, Catherine; Lu, Xiaojia; Wang, Yanxuan; Zuo, Xinyu; Li, Qiuyue; Huang, Zirui; Ma, Jianjun; Li, Pengyang
Abstract: Takotsubo cardiomyopathy (TCM), characterized by transient left ventricular dysfunction, was first reported in Japan in 1990. Current research suggests that TCM can be affected by conventional cardiovascular factors such as hypertension (HTN), diabetes, hyperlipidemia (HLD), and obesity. Despite the increasing interest in this disease, research on TCM remains limited. Conventional cardiovascular factors are clinically related to the outcome of TCM. We reviewed the publications published in PubMed database between January 01 2010 and January 15 2021, and summarized the most current available evidence on the correlation between TCM and the conventional cardiovascular factors. TCM patients are predominantly postmenopausal women. Men and young patients are less commonly seen, but are prone to acute adverse complications and poor prognosis. HTN is common in patients with recurrent TCM. Existing evidence suggests that obesity and chronic kidney disease are related to poor prognosis in TCM. HLD is reported to be associated with fewer complications, though current evidence is limited. Finally, the relationship between diabetes and TCM prognosis is ambivalent. Current evidence suggests conventional cardiovascular risk factors are associated with the outcome of TCM, especially with mortality and complications. More prospective studies are needed to clarify the relationship between each risk factor and the prognosis of TCM.